PENGARUH KINERJA, KEAMANAN, DAN MOTIVASI KARYAWAN PADA BUDAYA ORGANISASI DI SOCIAL CARE - Divania Fazrina; Edy Soesanto (CV. ADIBA AISHA AMIRA, 2023)
The phenomenon of employee performance, safety and motivation in Social Care organizations not meeting expectations. Low performance may be caused by a lack of training, skills development, this can include physical and non-physical problems such as workload stress, harassment, violence or discrimination. The purpose of this research is to identify the influence of organizational culture in Social Care organizations on employee performance, safety and motivation in the workplace.This research method is a convenience sampling technique and data analysis is carried out using descriptive statistical techniques. By involving 115 employees in the Social Care organization. From the results of this research data analysis, it shows that the influence of performance, safety and employee motivation has a significant impact on organizational culture in Social Care